2000
DOI: 10.1076/1385-4046(200005)14:2;1-z;ft196
|View full text |Cite
|
Sign up to set email alerts
|

Fractioning the Hooper: A Multiple-Choice Response Format

Abstract: The Hooper Visual Organization Test (HVOT) provides an excellent illustration of the multifactorial nature of most neuropsychological tests. Although the HVOT clearly requires certain visual perceptual skills, the test also demands that the subject produce an overt verbal response - i.e., the name of the object that has been cut up and rearranged. Thus, individuals with disorders of confrontation naming may obtain low scores on the HVOT by virtue of their anomia, even if the primary perceptual skills that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The object naming aspect of the VOT performance has also received critical review, since subjects that are intact to the visuospatial integration demands may score poorly if they suffer from compromised confrontational naming (Cirillo et al, 1999;Greve et al, 2000;Seidel, 1994). In an attempt to address this issue, a multiple choice derivative of the VOT has been proposed (Schultheis et al, 2000), and test results from the multiple-choice version indicated higher performance scores among anomic subjects.…”
Section: Introductionmentioning
confidence: 99%
“…The object naming aspect of the VOT performance has also received critical review, since subjects that are intact to the visuospatial integration demands may score poorly if they suffer from compromised confrontational naming (Cirillo et al, 1999;Greve et al, 2000;Seidel, 1994). In an attempt to address this issue, a multiple choice derivative of the VOT has been proposed (Schultheis et al, 2000), and test results from the multiple-choice version indicated higher performance scores among anomic subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Because the VOT comprises common, easily-named objects, the impact of naming might only be observed in individuals with significant anomia. This possibility is supported by a study of stroke patients with moderate to severe anomia that showed they were impaired on the standard version of the VOT, but significantly improved their performance on a multiple choice version that did not require naming (Schultheis, Caplan, Ricker, & Woessner, 2000).…”
Section: Discussionmentioning
confidence: 91%